J‐incision to approach the cranial abdomen in the adult horse. Issue 3 (24th February 2021) - Bauck, Anje G.; Nelson, Elizabeth; McLain, Andrew; Cock, Gemma; Sanchez, Linda C.; Freeman, David E.
Abstract: Objective: To describe a modified celiotomy to improve access to cranial abdominal structures in horses. Animals: Four horses. Study design: Short case series. Methods: Three horses with gastric impactions were treated with gastrotomies. One horse was treated for a diaphragmatic hernia with herniorrhaphy and mesh augmentation. In all horses, the ventral midline celiotomy was modified cranially with a J‐incision through the body wall, along the paracostal arch. Results: The only surgical complications were midline incisional infections in all horses. Three of the four horses had good long‐term outcomes; the remaining horse underwent euthanasia for reasons likely unrelated to incisional complications. Conclusion: The J‐incision improved access to the stomach and diaphragm in these horses. The paracostal component healed in all cases without evidence of infection or dehiscence. Clinical significance: This modified celiotomy may be considered to improve access during gastrotomy and repair of dorsally located diaphragmatic hernias.